2017
DOI: 10.1080/00461520.2017.1333430
|View full text |Cite
|
Sign up to set email alerts
|

Changing Teachers' Epistemic Cognition: A New Conceptual Framework for Epistemic Reflexivity

Abstract: There is increasing evidence to show that teachers' epistemic cognition is related to how they conceive of and engage in teaching; therefore it is important that teachers develop adaptive epistemic cognition. This article provides an overview of the different ways of theorizing and investigating changes in epistemic cognition for teaching and learning. A growing body of research shows that explicit reflection on epistemic cognition may be a useful way to promote change. Drawing on the work of Lunn Brownlee and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 46 publications
0
72
0
7
Order By: Relevance
“…Our results show that preservice teachers hold specific beliefs about the certainty of teaching knowledge, and that these beliefs may develop during teacher education (Lunn Brownlee et al, 2017;. The quantitative measure showed that preservice teachers' beliefs about the certainty of teaching knowledge changed from Time 1 to Time 2.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Our results show that preservice teachers hold specific beliefs about the certainty of teaching knowledge, and that these beliefs may develop during teacher education (Lunn Brownlee et al, 2017;. The quantitative measure showed that preservice teachers' beliefs about the certainty of teaching knowledge changed from Time 1 to Time 2.…”
Section: Discussionmentioning
confidence: 68%
“…The beliefs that preservice teachers hold about the certainty of teaching knowledge are likely to influence their learning and how they relate to different knowledge sources (Buehl & Fives, 2016;Bråten & Ferguson, 2015), as well as deep-learning and engagement in higherorder thinking, such as reflecting on knowledge and practice (Lunn Brownlee et al, 2017). This has consequences for the evidence-base of preservice teachers' future practice, as well as how they interact with their future students.…”
Section: Implications For Teacher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Each article argues the case for considering reflection, and more specifically epistemic reflexivity, in the context of teachers' epistemic cognitions. In the first article, "Changing Teachers' Epistemic Cognition: A New Conceptual Framework for Epistemic Reflexivity," Lunn Brownlee et al (2017/this issue) draw on the work of Archer (2010), Ryan and Bourke (2013), and previous conceptualizations by Lunn Brownlee and Schraw (in press) and Lunn Brownlee et al (2016) to propose the concept of epistemic reflexivity. Reflexivity involves critical thinking that evaluates multiple perspectives and leads to action in the classroom.…”
Section: Beyond Epistemic Reflection: a Focus On Epistemic Reflexivitymentioning
confidence: 99%